Saint John's Abbey Church : Marcel Breuer and the creation of a modern sacred space - Young, Victoria M., 1964- (University of Minnesota Press, 2014)
"In the 1950s the brethren at the Benedictine Abbey of Saint John the Baptist in Collegeville, Minnesota--the largest Benedictine abbey in the world--decided to expand their campus, including building a new church. From a who's who of architectural stars--such as Walter Gropius, Richard Neutra, Pietro Belluschi, Barry Byrne, and Eero Saarinen--the Benedictines chose a former member of the Bauhaus, Marcel Breuer. In collaboration with the monks, this untested religious designer produced a work of modern sculptural concrete architecture that reenvisioned what a church could be and set a worldwide standard for midcentury religious design. Saint John's Abbey Church documents the dialogue of the design process, as Breuer instructed the monks about architecture and they in turn guided him and his associates in the construction of a sacred space in the crucial years of liturgical reform. A reading of letters, drawings, and other archival materials shows how these conversations gave shape to design elements from the church's floor plan to the liturgical furnishings, art, and incomparable stained glass installed within it. The book offers a rare detailed view of how a patron and architect work together in a successful building campaign--one that, in this case, lasted for two decades and resulted in designs for twelve buildings, ten of which were completed. The post-World War II years were critical in the development of religious and architectural experiences in the United States--experiences that came together in the construction of Saint John's Abbey and University Church and that find their full expression in Victoria M. Young's account of the process. Using the liturgy of the mid-twentieth century as a cornerstone for understanding the architecture produced to support it, her book showcases the importance of modernism in the design of sacred space, and of Marcel Breuer's role in setting the standard."--